Capital Inflows and the Real Exchange Rate : Can Financial Development Cure the Dutch Disease? - Saborowski, Christian (IMF Working Papers; Working Paper ;, 2009)
This paper argues that, in improving the efficient allocation of resources, financial sector development could dampen the appreciation effect of capital inflows. Using dynamic panel data techniques, the paper finds that the exchange rate appreciation effect of FDI inflows is indeed attenuated when financial and capital markets are larger and more active. The main implication of these results is that one of the main dangers associated with large capital inflows in emerging markets-the destabilization of macroeconomic management due to a sizeable appreciation of the real exchange rate-can be mitigated partly by developing a deep financial sector.